High-performance, ultra-flexible and transparent embedded metallic mesh electrodes by selective electrodeposition for all-solid-state supercapacitor applications. Issue 19 (24th April 2017) - Liu, Yan-Hua; Xu, Jian-Long; Shen, Su; Cai, Xin-Lei; Chen, Lin-Sen; Wang, Sui-Dong
Abstract : High-performance, ultra-flexible and transparent embedded metallic mesh electrodes were fabricated via low-cost selective electrodeposition process combined with inverted film-processing methods for the first time. Flexible and transparent all-solid-state supercapacitors were thus successfully constructed. Abstract : A novel approach to fabricate large-scale embedded metallic mesh transparent conductive electrodes (TCEs) on flexible substrates via a low-cost and facile selective electrodeposition process combined with inverted film-processing methods is proposed for the first time. The optimized embedded Ni mesh TCEs on polyethylene terephthalate (PET) exhibit excellent optoelectronic properties ( R s ∼ 0.2 Ω sq −1 & T ∼ 84%), high figure of merit (FOM ∼ 1.0 × 10 4 ) and mechanical durability properties, which arise from the embedded inverted T-type shape of the electrodeposited Ni mesh. The resultant embedded Ni mesh/polymer poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hybrid electrodes are utilized both as current collectors and active electrode materials for all-solid-state flexible transparent supercapacitors, which show high transparency, superior electrochemical performances, excellent mechanical flexibility and high capacitance retention. Even after 1000 cycles of repetitive bending with a radius of 2 mm, the capacitance exhibited a decrease within only 5.2%. The high performance can be attributed to the excellent optoelectronic properties of embedded Ni mesh electrodes in combination with superior electrochemical properties of PEDOT:PSS. This provides a simple, cheap and controllable method for fabricating high-performance flexible TCEs and thus constructing flexible and transparent energy conversion and storage devices and systems.